Case Report: Macrophage Activation Syndrome and Widespread Neuroimaging Abnormality in Childhood-Onset Systemic Lupus Erythematosus - Shi, Nana; Wang, Xiangying; Zou, Lixia; Yang, Xinghui; Ma, Qian; Lu, Meiping (Frontiers in Pediatrics, 2021)
Macrophage activation syndrome (MAS) and wide-spread brain lesions are rare and severe complications of childhood-onset systemic lupus erythematosus (SLE). We report an 11-year-old girl who presented with recurrent rashes for half a year and fever for two weeks. Clinical and laboratory features at admission pointed to the diagnosis of SLE and SLE-associated MAS. Cerebral magnetic resonance imaging taken on day 4 after admission showed abnormal signals. Glucocorticoid therapy was started on day 5. Two days later the patient appeared neurologic disorders. High dose methylprednisolone, cyclophosphamide and intravenous immunoglobulin were used in the patient and intrathecal dexamethasone was given. The patient was discharged on day 30 after admission and showed complete clinical resolution and improved magnetic resonance imaging resolution.